2024
DOI: 10.3390/ijerph21030300
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minorities and Loneliness: Exploring Sexuality through Social Media and Gender–Sexuality Alliance (GSA) Supports

Linda Charmaraman,
Alice Zhang,
Kaitlyn Wang
et al.

Abstract: We examined online and offline social supports for sexual minority adolescents, underscoring the understudied developmental period of early adolescence and the mental outcome of loneliness. Stemming from a larger study in the northeast U.S., 967 youth participants were 26% sexual minority, 53% female, 45% male, and 2% other/nonbinary (mean age = 13.1, SD = 1.52). LGBTQ+ youth reported significantly higher levels of loneliness compared to their heterosexual counterparts. To understand potential sources of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Online communities can particularly benefit those who experience greater barriers accessing supports and services (e.g., rural and remote communities, marginalized groups), experience social anxiety, or are concerned about being stigmatized [34,35]. For instance, research suggests that people who identify as LGBTQ2S+ experience greater mental health benefits from active social media use compared to cisgendered people as it provides them an outlet for self-expression and access to social support they may not have access to offline [36,37]. Participants from our study mainly identified as LGBTQ2S+ (57%) and also expressed how TikTok helped them find communities they could relate to.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online communities can particularly benefit those who experience greater barriers accessing supports and services (e.g., rural and remote communities, marginalized groups), experience social anxiety, or are concerned about being stigmatized [34,35]. For instance, research suggests that people who identify as LGBTQ2S+ experience greater mental health benefits from active social media use compared to cisgendered people as it provides them an outlet for self-expression and access to social support they may not have access to offline [36,37]. Participants from our study mainly identified as LGBTQ2S+ (57%) and also expressed how TikTok helped them find communities they could relate to.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our findings represent the experiences of youth who mainly identified as white and women. Having a more ethnic-and gender-diverse sample could have provided further insights on youths' use of TikTok for mental health information as minority populations experience different access to mental health care and support compared to white, cis-gendered individuals [36,37].…”
Section: Discussionmentioning
confidence: 99%